222k views
0 votes
Drag the tiles to the boxes to form correct pairs. Match the pairs of equivalent expressions. please help ​

Drag the tiles to the boxes to form correct pairs. Match the pairs of equivalent expressions-example-1
User Alan Clark
by
6.1k points

1 Answer

7 votes

Answer:

(-9/2t + 3) +( 7/4t + 33) = -11/4t + 36

5(2t + 1)+(-7t +28) = 3t+ 33

Explanation

Those are the ones i could solve hope this helps!

1. Problem

(-9/2t + 3) +( 7/4t + 33)

-9/2t + 7/4t

-18/4t +7/4t= -11/4t

3+ 33= 36

-11/4t + 36

2. Problem

5(2t + 1)+(-7t +28)

10t + 5 + ( -7t +28)

10t - 7t= 3t

5+ 38= 33

User Umps
by
5.4k points